Exploring optimal paths, slope-dependent functions and digital elevation models in the greater Knossos area - Antoniadis , Vyron (Journal of Greek Archaeology, 2024)
In the aftermath of the Late Bronze Age (LBA), a period marked by a significant upheaval in the Aegean region, Knossos emerged as a resilient and stable settlement. This resilience is evident in the prosperity demonstrated in burials of that era. Recent archaeological finds from the Knossos Urban Landscape Project (KULP) suggest the presence of a substantial settlement during the Protogeometric (PG) period near the abandoned Minoan palace. Two methods of examining evidence contribute to our understanding of the spatial extent of the settlement: the ongoing study of the KULP survey pottery and spatial analysis of tomb clusters around the Early Iron Age (EIA) settlement. The Knossos Medical Faculty site (KMF), forming part of the extensive Knossos North Cemetery (KNC), stands out among burial groups by revealing the earliest and richest burials, alongside a concentration of later chamber tombs. Importantly, these EIA burial sites were established independently of Minoan cemeteries The distribution of EIA burial clusters, primarily chamber tombs, across the Knossian valley and low hills perplexed archaeologists. The topography of Knossos and the nature of its EIA settlement were initially deduced from the spatial distribution of cemeteries. Early interpretations proposed that scattered villages formed the town of Knossos, while others advocated for a small, nucleated settlement. The debate gained depth through the contributions of Antonis Kotsonas and Todd Whitelaw, who argued for a larger Knossos without associated hamlets, underlining the role of terrain morphology in burial site selection.